Folkloric Voices in Neorealist Cinema: The Case of Giuseppe De Santis (Sound Stage Screen, 2022)
Scholars agree that a fundamental incongruity lies at the core of neorealism’s “lack of audiophilia” (Sisto 2014). While neorealist directors aimed to bridge the gap between their films and the portrayed protagonists – notably marginalised, subaltern people –, the music and voices of the latter tended to be muted and disempowered by soundtracks that relied on well-established norms of film-scoring practices (Dyer 2006). This remark applies to several post-war Italian films, but the case of Giuseppe De Santis seems to complicate it. Through audiovisual analysis and the study of archival sources, this article examines how the director participated in the wave of rediscovery of folklore in post-war Italy, and how he contributed to the creation of (ambiguous) discourses about the folk’s voice, which leftist intellectuals regarded as the repository of anti-capitalist values.Firstly, I explore internal tensions in De Santis’ remediation of folk music. My analysis of the values attached to this repertoire in the rural film Caccia tragica (1947) shows that De Santis tended at once to affirm the “folk music vs capitalism” dichotomy, and to blur the line of such divide through several (involuntary?) short-circuits. The examination of these discursive fractures helps provide a nuanced understanding of the position occupied by folk music in post-war Italian cultural politics.Secondly, I claim that a comprehensive approach to film soundtracks may call into question the idea of neorealism’s indifference to the subalterns’ voice. Indeed, sound, more than music, proved essential for the director to try and empower the portrayed folkloric communities. I demonstrate the point by analysing the construction of folkloric soundscapes in Caccia tragica, where resonance is given to bells, whistles, and clapping that subvert the hegemonic world of the film’s villains. My account is complemented by a discussion of music and sound in Noi che facciamo crescere il grano (ca. 1953), one of De Santis’ unfinished projects.
Keywords: Folk music; Music in film; Sound studies; Remediation; Italian neorealism